2023
DOI: 10.1146/annurev-clinpsy-080921-074730
|View full text |Cite
|
Sign up to set email alerts
|

Racism and Social Determinants of Psychosis

Abstract: The Centers for Disease Control and Prevention has identified racism as a serious threat to public health. Structural racism is a fundamental cause of inequity within interconnected institutions and the social environments in which we live and develop. This review illustrates how these ethnoracial inequities impact risk for the extended psychosis phenotype. Black and Latinx populations are more likely than White populations to report psychotic experiences in the United States due to social determining factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 141 publications
1
7
0
Order By: Relevance
“…For example, research into disproportionate diagnosis of psychotic disorders among Black and Latinx individuals suggests likely systemic bias in clinical assessment (R. C. Schwartz & Blankenship, 2014;E. K. Schwartz et al, 2019) and increased exposure to psychosis risk factors associated with structural racism (Anglin, 2023;Shim, 2022). Within the current sample, nearly all participants received a lifetime diagnosis of BPD and ASPD, limiting statistical power to examine whether demographic groups were differentially likely to receive such diagnoses.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, research into disproportionate diagnosis of psychotic disorders among Black and Latinx individuals suggests likely systemic bias in clinical assessment (R. C. Schwartz & Blankenship, 2014;E. K. Schwartz et al, 2019) and increased exposure to psychosis risk factors associated with structural racism (Anglin, 2023;Shim, 2022). Within the current sample, nearly all participants received a lifetime diagnosis of BPD and ASPD, limiting statistical power to examine whether demographic groups were differentially likely to receive such diagnoses.…”
Section: Discussionmentioning
confidence: 85%
“…Various factors may contribute to differences in diagnostic rates and/or clinical presentation across social groups, including biases inherent in the definitions of disorder constructs (Metzl, 2010), bias on the part of diagnosticians (Garb, 2021; Shim & Vinson, 2021), or true differences in symptom manifestation that result from factors such as racism, minority stress, gender socialization, and culture (e.g., Anglin, 2023; DeVylder et al, 2023; Thomas et al, 2021). For example, research into disproportionate diagnosis of psychotic disorders among Black and Latinx individuals suggests likely systemic bias in clinical assessment (R. C. Schwartz & Blankenship, 2014; E. K. Schwartz et al, 2019) and increased exposure to psychosis risk factors associated with structural racism (Anglin, 2023; Shim, 2022). Within the current sample, nearly all participants received a lifetime diagnosis of BPD and ASPD, limiting statistical power to examine whether demographic groups were differentially likely to receive such diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Race is an important determinant of mental health and is not discussed in the Devanand and coauthors’ paper. Compared to Caucasians, Blacks in the United States and the UK are, respectively, 2.5 times and over 5 times more likely to be given a diagnosis of schizophrenia (Anglin, 2023; Halvorsrud et al ., 2019). Also, in the United States, Blacks have higher rates of psychotic symptoms in the general population.…”
Section: Race and Ethnicity Affect The Prevalence Of Psychosismentioning
confidence: 99%
“…Racial discrimination is positively associated with subthreshold psychotic experiences [17][18][19][20][21][22][23][24]. Findings from two epidemiological studies in the United States of America found that increased perceived racial discrimination was associated with higher auditory and visual hallucinations and delusional ideation [22].…”
Section: Racial Discrimination and Schizotypymentioning
confidence: 99%